Botulinum Toxin Recent Topics and Applications - Sabuncuoglu, Suna (IntechOpen, 2022)
Botulinum Toxin - Recent Topics and Applications provides doctors and researchers with the most up-to-date information on the structure and action of botulinum toxins as well as their usage to treat a wide range of disorders. The book covers the fundamentals of botulinum toxins, including improvements in our understanding of their molecular structure and mechanism of action. Furthermore, it covers the production and formulation of botulinum toxins for clinical applications. The information contained herein will hopefully shift the paradigm of botulinum toxin research, moving it away from a focus on toxin attributes toward a focus on toxin engineering based on patient requests and physician experiences in everyday practice.